2021
DOI: 10.1267/ahc.21-00090
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Expression of Pygo2 Correlates with Poorly Differentiated State Involving c-Myc, PCNA and Bcl9 in Myanmar Hepatocellular Carcinoma

Abstract: In Myanmar, hepatocellular carcinoma (HCC) is commonly seen in young adult and associated with poor prognosis, while the molecular mechanisms that characterize HCC in Myanmar are unknown. As co-activation of Wnt/β-catenin signaling and c-Myc (Myc) are reported to associate with malignancy of HCC, we immunohistochemically investigated the expression of Pygo2 and Bcl9, the co-activators of the Wnt/β-catenin signaling, Myc and PCNA in 60 cases of Myanmar HCC. Pygo2 expression was confirmed by in situ hybridizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…Meanwhile, downregulation of PYGO2 could inhibit HCC cell invasion in vitro and metastasis in xenograft tumor models, highlighting that targeting PYGO2 potentially inhibited metastasis of HCC. 13 , 20 , 21 In the present study, a potential interaction between EFNA4 and PYGO2 was predicted by Humanbase ( https://hb.flatironinstitute.org/ ), which was further verified using Co-IP assay. In addition, EFNA4 could positively regulate PYGO2 expression, and the results from following rescued experiments showed that simultaneous EFNA4 knockdown and PYGO2 overexpression recovered the phenotypes defect resulted from EFNA4 knockdown, suggesting that EFNA4 might exert its function in Huh7 cells partly by targeting PYGO2.…”
Section: Discussionsupporting
confidence: 54%
“…Meanwhile, downregulation of PYGO2 could inhibit HCC cell invasion in vitro and metastasis in xenograft tumor models, highlighting that targeting PYGO2 potentially inhibited metastasis of HCC. 13 , 20 , 21 In the present study, a potential interaction between EFNA4 and PYGO2 was predicted by Humanbase ( https://hb.flatironinstitute.org/ ), which was further verified using Co-IP assay. In addition, EFNA4 could positively regulate PYGO2 expression, and the results from following rescued experiments showed that simultaneous EFNA4 knockdown and PYGO2 overexpression recovered the phenotypes defect resulted from EFNA4 knockdown, suggesting that EFNA4 might exert its function in Huh7 cells partly by targeting PYGO2.…”
Section: Discussionsupporting
confidence: 54%
“…[18]. In hepatocellular carcinoma (HCC), Wnt/β-catenin and Myc signaling is upregulated that the correlative overexpression of nuclear PYGO2 and Myc represent the malignant characteristics of HCC [19]. In addition to the in vivo and in vitro functional assays, the clinical expression analysis discovered that high PYGO2 expression acts as an oncogenic driver of prostate cancer, which overexpression of PYGO2 protein was related to LNM and bone metastasis, high-grade cancer, and biochemical recurrence (BCR) [20].…”
Section: Discussionmentioning
confidence: 99%
“…In situ hybridization was performed as described previously ( Htun et al., 2021 , Koji and Brenner, 1993 ). Briefly, sections were deparaffinized, rehydrated, treated with 0.2 N hydrogen chloride for 20 minutes, and then treated with 50 μg/ml proteinase K (Wako, Osaka, Japan) at 37 °C for 15 minutes.…”
Section: Methodsmentioning
confidence: 99%